Maximum Entropy vector kernels for MIMO system identification. (May 2017) - Prando, Giulia; Chiuso, Alessandro; Pillonetto, Gianluigi
Abstract: Recent contributions have framed linear system identification as a nonparametric regularized inverse problem. Relying on ℓ 2 -type regularization which accounts for the stability and smoothness of the impulse response to be estimated, these approaches have been shown to be competitive w.r.t. classical parametric methods. In this paper, adopting Maximum Entropy arguments, we derive a new ℓ 2 penalty; to do so we exploit the structure of the Hankel matrix, thus controlling at the same time complexity, measured by the McMillan degree, stability and smoothness of the identified models. As a special case, we recover the nuclear norm penalty on the squared block Hankel matrix. In contrast with the previous literature on reweighted nuclear norm penalties, our kernel is described by a small number of hyper-parameters, which are iteratively updated through marginal likelihood maximization; constraining the structure of the kernel acts as a (hyper)regularizer which helps controlling the effective degrees of freedom of our estimator. To optimize the marginal likelihood, we adapt a Scaled Gradient Projection (SGP) algorithm which is proved to be significantly computationally cheaper than other first and second order off-the-shelf optimization methods. The paper also contains an extensive comparison with many state-of-the-art methods on several Monte-Carlo studies, which confirms the effectiveness of our procedure.